?? ????? ?????? ??????? ???????? ???????? Mondly "?????? ????? ????? ??????? ???????? ?????? "????? - Ririn Windasari; Wildan Mahsun Nurzaki (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2020)
In the learning process there is an interaction between teachers and students. This cannot be separated from the need for instructional media to support the continuity of learning. So that the knowledge conveyed by the teacher can be well received and can be practiced directly by students, especially in learning Arabic. Along with the times, applications that can be used to support the learning process are starting to emerge, it is fitting to use digital applications as a medium for learning Arabic. One of the applications that can be used is the Mondly application which can be operated on an Android phone. The teacher uses the Mondly application as a learning medium, and after being implemented at SMP Muhammadiyah 5 Surabaya, it is known that the use of the Mondly application for learning Arabic is effective with a comparison of the results of the T-test count between the pre-test and post-test.